Lump in a child’s toe - Teixeira, Susana Cláudia; Marinho, Pedro; Nogueira, Miguel; Machado, Susana (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
SE is a slow and benign growth of normal bone under the nail. The most common site is the hallux. This growth can cause nail disorders, masking the true problem and often leading to misdiagnosis. The pain caused by SE, especially with shoe contact, is significant and can affect the patient’s quality of life, so a prompt diagnosis is important.